Hubungan Tingkat Pendapatan terhadap Keberhasilan Pengobatan pada Pasien Tuberkulosis di Puskesmas Kecamatan Johar Baru Jakarta Pusat Tahun 2016 - Putri Mufrida Rahmah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2018)
Tuberculosis (TB), infection disease caused by M. tuberculosis, is a global challenge in health. TB can damage socially by causing stigma and isolation society also inflict financial loss. About 75% TB patients is productive ages economically (15-50 years old) and is estimated would lose working times 3-4 months and thus would lose their incomes about 20-30%. This study aims to determine the relation between incomes with the success of tuberculosis in treatment at Community Health Center of Johar Baru Central Jakarta in 2016. This study was done by analytical survey with cross sectional design. Population and sample are adult patients at Community Health Center of Johar Baru in 2016. Samples are selected using Simple Random Sampling. The data were collected by using questionnaires and crosschecked by looking at TB03 Card. Data was analyzed by using Chi Square test. There were 45 patients (80,4%) succeed in TB treatment and 32 patients (78%) have low incomes (<Regional minimum wage). Results from statistical tests using Chi Square test obtained P value = 0.115 (>0.05). There is no relation between incomes with the success of Tuberculosis treatment on Tuberculosis patients in Community Health Center of Johar Baru Central Jakarta in 2016.